Criminality, Poverty, and Unemployment in Aceh Province: Evidence from Granger Causality - Fachrurrozi, Kamal; Satria, Wisnu; Ichwan , Ichwan; Kadri, Mirzatul (Jurnal Samudra Ekonomika, 2025)
Criminality is one of the negative activities that emerge in social circles. The presence of criminality poses a challenge for policymakers because it disrupts public security and impacts economic stability. Forms of criminal activities include robbery, theft, gambling, murder, and corruption. The criminal cases in Aceh Province are quite serious. This study aims to analyze the relationship between criminality, poverty, and unemployment in Aceh Province. The research data was collected from 2010 to 2023. The research analysis method uses the Granger causality approach. The results of the study found that poverty has a one-way influence on criminality, criminality has a one-way influence on unemployment, and there is a two-way relationship between poverty and unemployment. Based on these findings, criminality, poverty, and unemployment need special attention. Policymakers need to provide support such as education, health, and welfare for the poor. In addition, there should also be available job opportunities in the informal sector to reduce unemployment rates.